PENGARUH UKURAN DEWAN KOMISARIS DAN UKURAN DEWAN DIREKSI TERHARAP NILAI PERUSAHAAN DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL MODERASI - Thendean, Claudia Adelina; Meita, Iren (EQUITY, 2018)
This study aims to determine the effect of Good Corporate Governance on Corporate Value with Intitusional Ownership as a moderating variable. In this study, Good Corporate Governance is measured by 2 variables, namely the size of the board of commissioners and the size of the boardof directors. The Company's value is measured by Earning Per Share. The sample of this research is 9 insurance companies listed on Indonesia Stock Exchange period 2011- 2015 period. The results of this study are the size of the board of commissioners and the size of the board ofdirectors does not affect the value of the company; The size of the board of commissioners and the size of the board of directors simultaneously has no effect on the value of the company; Institutional ownership may moderate the size of the board of commissioners to the value of thecompany; And institutional ownership can moderate the size of the board of directors against corporate value.